2009
DOI: 10.1016/j.biopsych.2008.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Atherosclerosis Covaries with Individual Differences in Reactivity and Functional Connectivity of the Amygdala

Abstract: Background-Cardiovascular disease (CVD) is a major source of medical comorbidity for patients with mood and anxiety disorders, and it remains the leading public health burden for the general population in industrialized nations. Indirect neurobiological evidence suggests that preclinical risk for atherosclerosis, the main contributor to CVD, may be conferred by interindividual variation in the functionality of the amygdala, a brain system jointly involved in processing behaviorally salient stimuli and regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 68 publications
3
57
2
Order By: Relevance
“…With respect to PTSD, an approach after acute trauma is the administration of glucocorticoids based on the counterintuitive findings that low normal glucocorticoid levels at the time of trauma predispose to development of PTSD symptoms (62). Increased amygdala reactivity to angry and sad faces is reported in individuals with early signs of cardiovascular disease (63), suggesting that the increased sympathetic activity and blood pressure reactivity may be a cause of allostatic load resulting from increased reactivity to daily experiences over time. Increased amygdala reactivity to faces has also been reported in individuals traumatized by 9/11 (64) as well as after sleep deprivation (65).…”
Section: Structural Plasticity In Other Brain Regionsmentioning
confidence: 99%
“…With respect to PTSD, an approach after acute trauma is the administration of glucocorticoids based on the counterintuitive findings that low normal glucocorticoid levels at the time of trauma predispose to development of PTSD symptoms (62). Increased amygdala reactivity to angry and sad faces is reported in individuals with early signs of cardiovascular disease (63), suggesting that the increased sympathetic activity and blood pressure reactivity may be a cause of allostatic load resulting from increased reactivity to daily experiences over time. Increased amygdala reactivity to faces has also been reported in individuals traumatized by 9/11 (64) as well as after sleep deprivation (65).…”
Section: Structural Plasticity In Other Brain Regionsmentioning
confidence: 99%
“…Low perceived social standing is associated with reduced PFC gray matter volume as well as with an increased systemic inflammatory tone and altered white matter structure throughout the brain (Gianaros et al, 2007(Gianaros et al, , 2013) and preclinical atherosclerosis is associated with increased amygdala reactivity to stimuli such as sad and angry faces and reduced inhibitory input from the PFC (Gianaros et al, 2009).…”
Section: Translation To the Human Pfcmentioning
confidence: 99%
“…For example, individual differences in amygdala reactivity to emotionally salient stimuli have been shown to covary with physiological parameters associated with cardiovascular disease risk, including basal levels of autonomic-cardiac control (42), stressor-evoked changes in blood pressure (43), and diurnal variations in the secretion of the stress hormone, cortisol (44). Recently, it has been demonstrated that individuals who express greater amygdala reactivity to threatening social cues (angry and fearful facial expressions) also exhibit higher levels of preclinical atherosclerosis (Figure 3) (45). In that study, individuals who showed lower levels of preclinical atherosclerosis exhibited a pattern of dynamic functional connectivity (correlated activity) between the amygdala and prefrontal cortex that suggested a potentially greater regulation of amygdala activity by the prefrontal cortex during threat processing.…”
Section: Brain Systems Mediating and Targeted By Allodynamic Processesmentioning
confidence: 99%